2004
DOI: 10.1002/ar.a.20105
|View full text |Cite
|
Sign up to set email alerts
|

GATA‐6 gene enhancer contains nested regulatory modules for primary myocardium and the embedded nascent atrioventricular conduction system

Abstract: The cGATA-6 gene is flanked by an enhancer that selectively marks the atrioventricular conduction system (AVCS) in transgenic mice. This enhancer reads anterior/posterior and medial/lateral positional information very early in the cardiogenic program and remains active in progressively more restricted regions of primary myocardium leading up to the emergence of a histologically distinct AVCS. We undertook to parse this enhancer to resolve how the respective AVCSspecific transcription program is regulated at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…The Cx30.2-enhancer in addition requires binding sites for T-box genes. 93 32,95 Together, these data indicate Tbx5 and Gata4 are responsible for Cx30.2 activity in the AVC. Tbx5 and Gata4 are expressed in both the AVC and working myocardium, 24,95 suggesting the existence of additional cofactors for AVC-restricted activity of Cx30.2 and the chicken Gata6-enhancer.…”
Section: Regulatory Dna Sequences Reveal Avc-specific Transcriptionalmentioning
confidence: 67%
See 1 more Smart Citation
“…The Cx30.2-enhancer in addition requires binding sites for T-box genes. 93 32,95 Together, these data indicate Tbx5 and Gata4 are responsible for Cx30.2 activity in the AVC. Tbx5 and Gata4 are expressed in both the AVC and working myocardium, 24,95 suggesting the existence of additional cofactors for AVC-restricted activity of Cx30.2 and the chicken Gata6-enhancer.…”
Section: Regulatory Dna Sequences Reveal Avc-specific Transcriptionalmentioning
confidence: 67%
“…17,24,75,[93][94][95] Cardiac troponin I and Gata6 are not specifically expressed in the AVC, indicating that these genes have multiple regulatory modules that define their complete pattern. In contrast to Tbx3 itself, the Tbx3 genomic fragment was not active in the AVB (Figure 5B), showing that gene expression in the AVC and the AVB depends on distinct regulatory sequences and pathways.…”
Section: Regulatory Dna Sequences Reveal Avc-specific Transcriptionalmentioning
confidence: 99%
“…the AVC, AVB) from early embryonic stages onwards (Davis et al, 2001). Within the enhancer, a core unit of 47 bp is sufficient to restrict the expression of a reporter gene to the AVCS (Adamo et al, 2004). Interestingly, the core enhancer is active in the entire heart tube, but during chamber differentiation becomes confined to the non-chamber myocardium, including the AVC (Christoffels et al, 2004b), suggesting that it is suppressed in the differentiating chamber myocardium.…”
Section: Regulatory Elements In the Ccs Transcriptional Networkmentioning
confidence: 99%
“…For example, expression of Nkx2.5 within the right ventricle, interventricular septum, and atrioventricular canal is controlled by enhancer modules that are distinct from those that direct expression in the atria (11). Likewise, enhancer sequences in the GATA6 locus that drive that gene's expression in conduction tissue differ from those responsible for expression within working myocardium (1,14). In these cases, it is important to realize that the expression profile of a reporter transgene under control of individual enhancer modules does not necessarily correspond to domains exhibiting higher levels of expression of the endogenous gene.…”
mentioning
confidence: 99%
“…This genetic region contains consensus binding sites for several heart-associated factors, including Nkx2.5, MEF2C, SRF, GATA-4/5/6, HAND1, and Hand2 (15), whose combination may account for the differential activity of this enhancer (1,15). Previous studies (15) examining development of these mice demonstrated that lacZ expression driven by this GATA6 distal enhancer is associated with the developing myocardium.…”
mentioning
confidence: 99%